1986
DOI: 10.1128/mcb.6.11.3685
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic gene conversion lengths, coconversion patterns, and the incidence of reciprocal recombination in a Saccharomyces cerevisiae plasmid system.

Abstract: Plasmids capable of undergoing genetic exchange in mitotically dividing Saccharomyces cerevisiae cells were used to measure the length of gene conversion events, to determine patterns of coconversion when multiple markers were present, and to correlate the incidence of reciprocal recombination with the length of conversion tracts. To construct such plasmids, restriction site linkers were inserted both within the HIS3 gene and in the flanking sequences, and two different his3-alleles were placed in a vector. Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
45
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 28 publications
4
45
0
Order By: Relevance
“…Second, examination of independent events showed that the frequency with which each of the two HIS3 heteroalleles was converted to the wild type remained nearly constant in all the constructions. (As previously reported [1], a slight preference for conversion of the allele on the side of the plasmid close to the ampicillin marker exists no matter whether the heteroallele is the 5' or 3' member of the pair.) Limitations in homology which would diminish initiation would be expected to decrease the frequency with which the allele nearest the homology border is converted.…”
Section: Methodsmentioning
confidence: 59%
See 4 more Smart Citations
“…Second, examination of independent events showed that the frequency with which each of the two HIS3 heteroalleles was converted to the wild type remained nearly constant in all the constructions. (As previously reported [1], a slight preference for conversion of the allele on the side of the plasmid close to the ampicillin marker exists no matter whether the heteroallele is the 5' or 3' member of the pair.) Limitations in homology which would diminish initiation would be expected to decrease the frequency with which the allele nearest the homology border is converted.…”
Section: Methodsmentioning
confidence: 59%
“…From left to right, the ratios are for the following sets of markers: the SmaI marker in pKD40 versus that in pBYA819 and pBYA918; the SmaI marker in pKD90 versus that in pBYA819 and pBYA918; the second ClaI marker to the 3' side in pBYA229 and pBYA209 versus that in pBYA219 and pBYA239; the Sacl marker to the 5' side in pBYA239 and pBYA209 versus that in pBYA219 and pBYA229; the SmaI marker in pKD400 versus that in pBYA819 and pBYA918; and the first Clal marker to the 3' side in pBYA229 and pBYA209 versus that in pBYA819 and pBYA918. The data for plasmids pBYA819 and pBYA918 are from our previous report (1). the rates, which are measures of exchange within the HIS3 gene, were not clearly diminished by the changes in the position of the homology border suggests that the same number of events were initiated in cases in which borders were closer to flanking markers as in cases with more extended homology.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations